INVESTIGATION OF HYDROGEOLOGICAL AND ENVIRONMENTAL CONDITIONS WITH RESPECT TO THE EXISTANCE OF A CEMETERY WITHIN THE REGION OF THE LIVADIA VILLAGE AT THE ISLAND OF TlLOS - Περλέρος B.; Αντωνιάδης Κ.; Δρακοπούλου E. (Bulletin of the Geological Society of Greece, 2004)
The hydrogeological and environmental conditions were investigated, as dictated by national legislation, in order to define the boundaries of the Livadia village, at the island of Tilos. However, since a cemetery is located near the village, an additional study had to be performed, to estimate the possibility to decrease the distance required by law (250 m), between the cemetery and the village boundaries. This study investigated the impact of the cemetery on groundwater and surrounding environment by utilizing the geological, hydrogeological, environmental and chemical data in order to: • Evaluate the significance of underground water according to national and international standards. • Evaluate the flow of underground water. • Evaluate the chemistry of underground water upgradient, downgradient and near the cemetery. • Evaluate the possibility of compound and microbiological load migration from the cemetery and downgradient towards the village. • Locate other possible sources of contamination within the wider area of investigation. • Estimate the influence of the cemetery on surface and underground water • Recommend a groundwater monitoring system.